DFT investigation of the reaction mechanism for the guanidine catalysed ring-opening of cyclic carbonates by aromatic and alkyl-amines. Issue 31 (31st March 2017) - Alves, M.; Méreau, R.; Grignard, B.; Detrembleur, C.; Jérôme, C.; Tassaing, T.
Abstract : The bifunctional activity (base/H-bond donor) of TBD allows understanding its higher efficiency compared to its methyl counterpart (MTBD) for the aminolysis of cyclic carbonates by amines. Abstract : The guanidine catalysed aminolysis of propylene carbonate has been investigated using density functional theory (DFT) and highlights that different reaction pathways are involved, depending on the aromatic or aliphatic nature of the amine. The structural ability of 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) to simultaneously give and receive protons was demonstrated by a detailed mechanistic investigation. The bifunctional activity (base/H-bond donor) of TBD significantly reduces the Gibbs energy of the reaction and allows understanding of its higher efficiency compared to its methyl counterpart (MTBD).